2018
DOI: 10.1038/s41467-017-02494-0
|View full text |Cite
|
Sign up to set email alerts
|

Dysbindin links presynaptic proteasome function to homeostatic recruitment of low release probability vesicles

Abstract: Here we explore the relationship between presynaptic homeostatic plasticity and proteasome function at the Drosophila neuromuscular junction. First, we demonstrate that the induction of homeostatic plasticity is blocked after presynaptic proteasome perturbation. Proteasome inhibition potentiates release under baseline conditions but not during homeostatic plasticity, suggesting that proteasomal degradation and homeostatic plasticity modulate a common pool of vesicles. The vesicles that are regulated by proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 63 publications
(108 reference statements)
4
72
0
Order By: Relevance
“…This either 606 favors the hypothesis that acute homeostatic plasticity is accomplished by distinct 607 molecular mechanisms or, in line with the aforementioned findings, is restricted to type 608 Ib terminals. Wentzel et al, 2018 demonstrated that synaptic vesicles recruited from 609 vesicle pools during acute homeostatic plasticity are highly sensitive to EGTA. 610…”
mentioning
confidence: 99%
“…This either 606 favors the hypothesis that acute homeostatic plasticity is accomplished by distinct 607 molecular mechanisms or, in line with the aforementioned findings, is restricted to type 608 Ib terminals. Wentzel et al, 2018 demonstrated that synaptic vesicles recruited from 609 vesicle pools during acute homeostatic plasticity are highly sensitive to EGTA. 610…”
mentioning
confidence: 99%
“…These data suggest that presynaptic proteasomal degradation has the capacity to regulate Ca 2+ influx. Reprinted and adapted from (Wentzel et al, 2018)…”
Section: Physiology and Genesmentioning
confidence: 99%
“…One of the recently discovered genes promoting tight coupling and PHP is fife, a Drosophila Piccolo-RIM homolog (Bruckner et al, 2017; Figure 3a). In addition to tightly-coupled synaptic vesicles, recent experimental evidence suggests a role for "loosely-coupled" vesicles in PHP (Wentzel, Delvendahl, Sydlik, Georgiev, & Müller, 2018).…”
Section: Physiology and Genesmentioning
confidence: 99%
See 2 more Smart Citations